The Role of Terminology Preparation in Enhancing Interpreters’ Performance - Abusaada, Husam; Hassan, Ahmed Thalal Bin; Mohamed, Amaal Fadhlini Binti (Journal of Posthumanism, 2025)
This study investigates the effect of terminology preparation on the interpreter’s performance, focusing on a politically complex topic namely annexation. Fifty undergraduate students enrolled in an interpreting course at the Department of English, Al-Azhar University-Gaza participated in a quasi-experimental pre-test/post-test design. Participants first completed an interpreting test administered online due to the ongoing war. Then, they were given a 15-page bilingual glossary containing key terms related to annexation. Afterward, they completed the same interpreting test. The results were analyzed using SPSS, and revealed a statistically significant improvement in performance regarding the terminology preparation, with mean scores increasing from 6.32 to 9.48 (p < .001). Although the results show a low pre/post-test correlation, the findings indicate that the glossary intervention had a strong and meaningful effect across all performance levels. This study highlights the pedagogical value of structured terminology preparation in interpreter training, particularly under crisis conditions and in under-resourced environments.